Inflammatory state moderates response to cannabis on negative affect and sleep quality in individuals with anxiety - Lisano, Jonathon K.; Skrzynski, Carillon J.; Giordano, Gregory; Bryan, Angela D.; Bidwell, L. Cinnamon (Frontiers in Behavioral Neuroscience, 2025)
IntroductionInflammation has been implicated as an underlying pathology in negative affect and sleep disruption. Cannabinoids like delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) have demonstrated anti-inflammatory properties. This study aimed to assess if cannabis use altered cytokine concentration and whether inflammatory status moderated the influence of 4 weeks of cannabis use on negative affect and sleep quality in anxious individuals.MethodsParticipants with mild or greater anxiety (n = 147) were assigned to one of three cannabis chemovars (THC + CBD, THC, CBD), asked to consume their products ad libitum for 4 weeks, and were compared to a group of participants with anxiety who did not use cannabis (n = 24). Measures of negative affect (Depression Anxiety and Stress Scale-21: DASS-21), sleep quality (Pittsburgh Sleep Quality Index: PSQI), and plasma cytokine concentrations were measured at Baseline and Week-4. Multilevel modeling assessed if there were group-dependent changes in cytokine concentrations over time, and whether baseline inflammation moderated the association between cannabis use and both negative affect and sleep quality.ResultsThere were no group-dependent changes in cytokine concentrations throughout the study (p = 0.12). It was observed that baseline inflammatory state moderated the group-by-time relationship for DASS-21 (p < 0.001) and PSQI (p = 0.04). In both models, chemovars higher in CBD produced more consistent improvements, while THC-associated improvements varied by baseline inflammatory state.ConclusionThese novel findings suggest that baseline inflammatory status influences the relationship between cannabis use, negative affect, and sleep quality in people with anxiety.